Leiomyoma of The Vagina - Cüneyt Eftal Taner; İrem Şenyuva; Yusuf Yıldırım; Volkan Atalay; Akın Yaman (Medical Network, 2008)
17 year old girl complaining of pelvic swelling mass and urinary frequency was reported. Ultrasonography and abdominal computed tomography showed a solid mass with size of 130x121x117 mm in left pelvis, normal sized uterus.At laparotomy there was solid mass under the bladder located at the left anterior part of the elevated uterus. With an incision at the anterior serosa of the uterus the bladder was removed. There was a vaginal myoma at the base seperate from the uterus. Second insicion was performed to the left anterior vaginal wall, mass enucleated from its base. Four units of blood was required intra and postoperatively. İn large vaginal leiomyomas located in the upper part of the vagina combined abdominovaginal approach may be prefferred for providing safer operation with less bleeding.